2018
DOI: 10.1016/j.bone.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of hip fractures across western Victoria, Australia

Abstract: Crude incidence rates varied by location. Given that a high proportion of patients had acute hospital care of ≤14days, and accessibility and SES were associated with hip fracture rates, these results can inform policy and provide a model for other groups to conduct similar research in their local environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…In our study, this plateauing incidence was very different from the previous rapid increase reported by Xia et al in Beijing, China [ 16 ], or the pattern found in other low- or intermediate-income nations such as South Africa [ 14 ] and Kuwait [ 15 ]. However, most high-income nations, such as the US [ 8 ], Canada [ 9 ], Finland [ 10 ], France [ 11 ], Australia [ 12 ], and Sweden [ 13 ], have reported a plateau or continuing decline after an initial increase. A similar pattern of age-adjusted incidence lagging about 1 decade behind that of high-income countries was also found in Taiwan [ 35 ] and Hong Kong [ 36 ], 2 other economically advanced regions in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, this plateauing incidence was very different from the previous rapid increase reported by Xia et al in Beijing, China [ 16 ], or the pattern found in other low- or intermediate-income nations such as South Africa [ 14 ] and Kuwait [ 15 ]. However, most high-income nations, such as the US [ 8 ], Canada [ 9 ], Finland [ 10 ], France [ 11 ], Australia [ 12 ], and Sweden [ 13 ], have reported a plateau or continuing decline after an initial increase. A similar pattern of age-adjusted incidence lagging about 1 decade behind that of high-income countries was also found in Taiwan [ 35 ] and Hong Kong [ 36 ], 2 other economically advanced regions in China.…”
Section: Discussionmentioning
confidence: 99%
“…It is projected that the number of hip fractures worldwide will increase from 1.26 million in 1990 to 4.5 million by 2050, about half of which are likely to occur in Asia, and particularly in China [1]. However, in the past decade, the incidence of hip fracture in high-income nations has declined or reached a plateau after an initial increase [8][9][10][11][12][13]. The vast majority of published studies have been conducted in high-income nations, and the data are scarce in low-or intermediate-income nations [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The OR can be used to estimate RR when the disease is not common in the studied population (the incidence of the disease less than 10%). As far as we know, the incidence rate of all types of fragility fracture in population over 50 years old was far below 10% [3,[63][64][65]. Herein, the ORs are approximated to the RRs in our meta-analysis [66].…”
Section: Discussionmentioning
confidence: 99%
“…Proximal femur fractures, commonly referred to as hip fractures, constitute one of the largest challenges to modern health care (Cheung et al, 2018;Holloway et al, 2018). With millions of cases worldwide every year (Ström et al, 2011), hip fractures are a significant economic and social concern (Hernlund et al, 2013).…”
Section: Introductionmentioning
confidence: 99%